Penyuluhan Kesehatan Peduli Remaja Terhadap Pengetahuan Dan Sikap Remaja Tentang Seks Pranikah - Christina Pernatun Kismoyo (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: World Health Organization (WHO) in 2010 to 210 million each year for pregnant teenagers aroundthe world, 46 million of them have an abortion because of the sex before marriage. One of the causes of pregnancyoutside of marriage is the inability of a teenager in a biological impulse control. From the data of the Ministry of Religious Bantul increasing cases of early marriage, and 95% of early marriage are caused by premarital pregnancy.Objective: To identify the level of knowledge and attitudes of teenagers in the village Girirejo premarital sex beforeand after counseling.Methods: This study used a quasi-experimental (quasi experiment) with the approach of one group pretest-posttestwith a till sample with purposive sampling method 56 adolescent youth village Girirejo, Imogiri and analyzed datawas analyzed by paired sample t-test with SPSS for windows 17.0 statistical test decision to use a significant levelof p <0.05.Results: An increase in knowledge and attitudes about premarital sex teens toward better after counseling. Thetest results obtained on the effects of counseling for adolescent knowledge and attitudes about premarital sex witha value of p = 0.001 <α = 0.05 is generated average value knowledge and attitudes 2857 -2321Conclusions and suggestions: Method PKPR effective counseling in improving knowledge and attitudes aboutpremarital sex in adolescents Girirejo village, Imogiri. Activity PKPR the health center used as a routine activity forat least 6 months and the village provides good support infrastructure and funding. Mental revolution to create ageneration that is clean, healthy, and strong in building the nation.Keywords: Education, knowledge, attitudes premarital sex, PKPR.